1970
DOI: 10.5962/bhl.part.75902
|View full text |Cite
|
Sign up to set email alerts
|

Das Verhalten von Cuniculus paca (Rodentia, Dasyproctidae) in Gefangenschaft

Abstract: Systematisch-biologische EinleitungCuniculus ist eine neotropische Gattung von Nagern mit einem Verbreitungsgebiet, das von Mexiko bis nach Argentinien reicht. Moojen (1952) erkennt zwei Formen von Paka: eine kontinentale, C. paca paca (L.) und eine insulare Form, C. paca mexianae (Hagmann), die sich osteologisch voneinander unterscheiden. Cabrera ( 1 96 1 ) zieht für die Gattung den Namen Agouti (Lacépède) aus Prioritätsgründen vor und erfasst drei Formen: A. paca paca (L.) mit typischem Fundort in Cayena und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

1974
1974
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 1 publication
0
3
0
2
Order By: Relevance
“…In the wild, paca are strictly nocturnal (Beck‐King et al., ), spending the day in dens (Pérez, ) where they most likely also practice caecotrophy. Different reports have shown that in captivity, paca maintain their nocturnal activity pattern, practicing caecotrophy mainly during daylight hours (Sabatini & Paranhos Da Costa, ), or that an individual animal can shift towards daytime activity due to the respective management routine (Pilleri, ) but revert to nocturnal activity when this routine is changed again (Kraus et al., ). The periods during which the pacas practice caecotrophy can change correspondingly, and the behaviour only occurred during nighttime hours in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the wild, paca are strictly nocturnal (Beck‐King et al., ), spending the day in dens (Pérez, ) where they most likely also practice caecotrophy. Different reports have shown that in captivity, paca maintain their nocturnal activity pattern, practicing caecotrophy mainly during daylight hours (Sabatini & Paranhos Da Costa, ), or that an individual animal can shift towards daytime activity due to the respective management routine (Pilleri, ) but revert to nocturnal activity when this routine is changed again (Kraus et al., ). The periods during which the pacas practice caecotrophy can change correspondingly, and the behaviour only occurred during nighttime hours in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…There is some discrepancy in the literature as to whether pacas ( Cuniculus paca ) practice caecotrophy. Kraus, Gihr, and Pilleri () proactively claimed that paca do not practice caecotrophy. Matamoros () observed that captive paca sometimes eat faeces deposited on the floor.…”
Section: Introductionmentioning
confidence: 99%
“…We refer to this strategy as '(separation mechanism-based) coprophagy'; it is not necessarily compulsory but may be negligible under certain conditions of dietary nutrient provision [49]. The human reluctance to accept this strategy [4] is mirrored in historical sequences of publications that first claimed that a species did not practice coprophagy or considered it a pathology, then reported sporadic 'normal' observations, and finally accepted the strategy as a characteristic of the species, as exemplified in nutria (Mycastor coypus) [50][51][52][53][54], paca (Cuniculus paca) [55][56][57][58][59], capybara (Hydrochoerus hydochoeris) [60,61] or the gerbillinae [62][63][64].…”
Section: (D) Mammalian Microbe Farmingmentioning
confidence: 99%
“…Estas posturas são semelhantes às observadas por Kraus et al (1970), em suas pesquisas com rodentia. Santos ( 2005) estudando a ecologia de Dasyprocta leporina em um fragmento florestal, observou que esses animais dedicavam parte do tempo para descansar, principalmente no final da manhã e início da tarde, onde o comportamento deitado foi registrado com 15,06 % de frequência.…”
Section: Pubvetunclassified
“…Rosenbaum et al (2009), em seus estudos com roedores, relataM que a preferência pelo tipo de material utilizado como cama pode variar bastante, não apenas em relação ao material, mas também à forma como este é disponibilizado. Kraus et al (1970) realizando pesquisas com rodentia, resgistram que a coleta de material é realizada somente pela boca e as mãos não são usadas neste contexto comportamental. Nossas análises são semelhantes a esta observação constatada anteriormente, sendo esta coleta normalmente individual, ocorrendo de forma aleatoria e pouco frequente.…”
Section: Coleta E Transporte De Materialsunclassified